Age at Onset and Social Cognitive Impairment in Clinically Stabilized Patients with Schizophrenia: An Ecological Cross-Sectional Study - Massimiliano Buoli; Alice Caldiroli; Marta Serati; Giulia Orsenigo; Elisabetta Caletti (Iranian Journal of Psychiatry, 2018)
Objective: Purposes of the present study were to assess the social cognitive impairment in schizophrenia and to detect if some clinical variables (particularly age at onset) are predictive of general/social cognitive deficit in schizophrenia patients.